Plateaus of freedom : nationality, culture and state security in Canada, 1940-1960 - Kristmanson, Mark, 1960- (Canadian social history series., 2014)
The security and cultural policy measures examined here, from the RCMP investigations at the National Film Board that led to numerous firings, to the harassment of the extraordinary African-American singer and Soviet sympathizer Paul Robeson, 'attest to the fragility and the enduring power of art to effect social change'.